Escassez de força de trabalho: Uma revis\~ao da literatura internacional e interpretaç\~ao dos resultados empíricos referentes ao Brasil - Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper presents an international literature review on qualified labor shortage and summarizes recent evidence on this topic in the context of Brazilian labor markets. An interpretation is provided on the extent of this problem in Brazil in the 2000s. It does not seem to be the case that a general workforce shortage took place in Brazil in that period - at least not among the more educated workers. Nonetheless, some mismatch may have occurred. The problem might have affected specific industries experiencing strong and fast growth back then, as well as those highly dependent on less educated workforce. Moreover, difficulties to fill vacancies may have emerged due to some possible developments not directly related to the lack of individuals with minimal credentials available in the labor market. In a decade of high levels of employment, Brazilian firms seem to have foreseen some lack of soft skills (e.g. leadership) and of other non-education-related attributes (e.g. large experience) as a sign of general workforce shortage. Vacancies requiring highly specialized skills, as well as those available far from major urban centers as a result of new investments, common in years of higher economic growth, may have intensified the perception of a general shortage. However, these are usually short run mismatches and are likely to be solved rather by customized short courses and/or market and regulation mechanisms than by increasing graduate flows. Long run initiatives should be more focused on improving all levels of the currently low-quality Brazilian education system - which affects the performance of the workforce and their productivity at all times, whether or not quantitative shortages are likely to take place. Delimitating the problem accurately is important to avoid inappropriate policy targeting.
Keywords: J21; J24; 330; workforce shortage; Brazil; literature review